2001
DOI: 10.1034/j.1600-0609.2001.066006396.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of intraplatelet calcium concentration affect the binding of thrombospondin to blood platelets in healthy donors and patients with type 2 diabetes mellitus

Abstract: Both the release of TSP and CD36 presentation are under the influence of agents modulating intracellular Ca2+. Diabetic platelets seem more vulnerable to the releasers of cytosolic [Ca2+] and more resistant to the blockers of cytosolic [Ca2+] mobilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These results are also in agreement with the studies by others [9]. CD36 is expressed in resting cells and its amount significantly increased after agonist stimulation [11], which was also observed in this study. We demonstrated that the 5-min incubation of whole blood with simvastatin and pravastatin significantly decreased CD36 expression in collagen-or ADP-agonized platelets in healthy volunteers.…”
Section: Discussionsupporting
confidence: 94%
“…These results are also in agreement with the studies by others [9]. CD36 is expressed in resting cells and its amount significantly increased after agonist stimulation [11], which was also observed in this study. We demonstrated that the 5-min incubation of whole blood with simvastatin and pravastatin significantly decreased CD36 expression in collagen-or ADP-agonized platelets in healthy volunteers.…”
Section: Discussionsupporting
confidence: 94%
“…Due to enhanced Ca +2 mobilisation in platelets of diabetic patients, TSP release and binding is likely to be augmented in diabetes. The altered release and binding of TSP to platelets from diabetic patients and its relevance to the impaired platelet calcium mobilisation in the presence of calcium modulators has been suggested [124,141,149,167,170,171]. The incidental reports have suggested that level of TSP bound to circulating platelets is elevated not only in IDDM patients with diabetic cardiovascular microangiopathy, but also those with newly diagnosed diabetes [170,171].…”
Section: Thrombospondinmentioning
confidence: 94%
“…In the course of platelet activation TSP becomes released from intraplatelet granules and the ongoing Ca 2+ mobilisation and its traffic outside platelets facilitates TSP binding to platelet surface membranes. Thus, Ca 2+ mobilisation and release in diabetic platelets support TSP binding in a double way: indirectly, via enhancing Ca 2+ -depended cellular signaling, and directly -via promoting the interaction of TSP with its receptor(s) [167].…”
Section: Thrombospondinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the importance of CD36 in atherogenesis has been demonstrated, since transgenic mice with a deletion of both Cd36 and apoE develop 77% less lesion area than control apoE knockout mice (21). Given that CD36 expression has been reported to be similar in platelets from humans with type 2 diabetes and controls (36), it is plausible that the high levels of markers of platelet activation in type 2 diabetes (3-5) result from triglyceride-enhanced platelet activation via CD36 rather than changes in platelet CD36 expression per se.…”
Section: Cd36 Vldl and Platelet Activationmentioning
confidence: 99%